Playing with one’s self: notions of subjectivity and agency in digital games - Charles, Alec (Eludamos: Journal for Computer Game Culture, 2009)
This paper explores the ways in which the experience of participation or interactivity in digital games may influence or reinvent the player’s ideological subjectivity. It offers an application to video game analysis of the theoretical perspectives of Jean Baudrillard, Roland Barthes, Louis Althusser, Theodor Adorno, Walter Benjamin and Slavoj Žižek, and thereby suggests that the simulated realities of commercial digital games cultures offer an illusion of agency or co-authorship which, in common with similar illusions promoted by parallel manifestations of industrial mass culture, may foster a critical complacency which permits the inscription of their consumers within virtually invisible ideological perspectives.